2023
DOI: 10.3390/life13020335
|View full text |Cite
|
Sign up to set email alerts
|

Complicated Relationships between Anterior and Condylar Guidance and Their Clinical Implications—Comparison by Cone Beam Computed Tomography and Electronic Axiography—An Observational Cohort Cross-Sectional Study

Abstract: A complex prosthodontic treatment is believed to be more successful when the condylar path is replicated using the articulator. However, there is an ongoing major disagreement between the researchers as the exact relationship between the posterior and anterior determinants has not been clear. The purpose of this study was to investigate whether the protrusive movement of the mandible does correlate with the temporomandibular joint (TMJ) anatomy or with incised features. Subjects (15 males and 15 females) were … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
0
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 55 publications
0
0
0
Order By: Relevance
“…Han et al demonstrated weak but statistically significant correlations between the incisal angle, the size of the condyle and glenoid fossa. On the other hand, other studies concluded that the shape variation of the fossa and condyle was not related to the occlusal plane angle and incisal guidance angle (40) and consequently teeth morphology does not affect the TMJ formation in young adults (41).…”
Section: Correlation Test Between Mean Values Of the Left-right Measu...mentioning
confidence: 92%

None

HOSHYARI,
ZAMANIAN,
SAMII
et al. 2023
Maedica
“…Han et al demonstrated weak but statistically significant correlations between the incisal angle, the size of the condyle and glenoid fossa. On the other hand, other studies concluded that the shape variation of the fossa and condyle was not related to the occlusal plane angle and incisal guidance angle (40) and consequently teeth morphology does not affect the TMJ formation in young adults (41).…”
Section: Correlation Test Between Mean Values Of the Left-right Measu...mentioning
confidence: 92%

None

HOSHYARI,
ZAMANIAN,
SAMII
et al. 2023
Maedica
“…CBCT is a cutting-edge technology that provides multiplanar segments in three dimensions without superimposition. However, CBCT exposes the patient to ionizing radiation, making it necessary to weigh the benefits against the potential risks (8) .…”
Section: Introductionmentioning
confidence: 99%
“…In the dynamic and complex field of temporomandibular disorders (TMDs), keeping our knowledge up to date is of great importance. The following Special Issue focuses on novel as well as established therapies [1][2][3][4][5][6], with an additional glimpse at diagnostic improving tools and novel approaches [4,7,8], as well as epidemiological data [9].…”
mentioning
confidence: 99%